Finnair competitive advantage through environmental responsibility - Baumeister, Stefan (2011)
Air transportation plays a vital role in many aspects of our every day life. Due to strong growth and the increasing amount of green house gases released, the aviation industry cannot be considered as operating sustainable. To change this all stakeholders of the aviation industry have to act. A special role hereby play the airlines as they can most directly influence the amount of green houses gases released e.g. by operating modern and fuel efficient aircraft. Offering flights that are producing less emissions has its price as e.g. acquiring modern aircraft can be very costly. At the same time competition between airlines is getting continually tougher forcing also established airlines to cut back their costs. The idea of this research is therefore to study how an airline could turn these additional investments into a competitive advantage factor instead of just seeing the costs and risks. One airline which has shown strong commitment to cut back green house gas emissions in the recent years is Finland’s largest airline Finnair. The purpose of this study was to find out how Finnair could gain competitive advantage through its environmental performance. Therefore Finnair’s customer’s opinions and attitudes towards environmental aspects of flying have been studied and analysed with the help of a web-based questionnaire. The results showed that there are air passengers who consider the environment when booking a flight although this was not the majority. The study also found that Finnair’s customers value the fact that Finnair is operating a modern fleet and is offering them the shortest routes but not all of them were ready to pay more for that. The research also detected that many Finnair customers are not aware of Finnair’s outstanding environmental performance. It can therefore be concluded that Finnair should more actively communicate its environmental work to attract new customers and to gain competitive advantage.